The Effect of Legislative Bargaining Power on Asymmetric Budget Ratcheting in Local Governments - Siti Nur Azizah Salsabila; Dyah Setyaningrum (Jurnal Ilmiah Akuntansi Kesatuan, 2026)
In many decentralized systems, local governments face persistent challenges in aligning fiscal discipline with political and administrative incentives. This study examines the persistence of asymmetric budget ratcheting in Indonesian local governments following the enactment of Law Number 1 of 2022 on Fiscal Relations between the Central and Regional Governments. Despite mandates for performance-based budgeting, incrementalism remains prevalent. The research analyzes how legislative bargaining power, shaped by political coalition dynamics, influences budget adjustments. Using a longitudinal quantitative dataset of 508 regencies and cities, the study employs panel data regression and Structural Equation Modelling (SEM) to assess budget reactivity. The findings show a pronounced asymmetric pattern, future budgets increase by 99.7% of overspending variance but decrease by only 21% of underspending variance. SEM results indicate that legislative bargaining power significantly affects budget variance, supporting opportunistic target-setting behavior. Sub-sample analyzes reveal that budget ratcheting is most dominant in regions with high fiscal capacity and strong managerial capabilities, where performance information is strategically used to justify budget increases. The evidence suggests that political affiliations act as a key driver of incremental budget growth, weakening the intended effects of performance-based budgeting reforms and undermining technical efficiency goals.